May : rapsodia infantil ; ¡Miau! : historia del gatito misceláneo / Joaquín Maurín ; prefacio de Mario Maurín - Maurín, Mario (1928-2014); Maurín, Joaquín (1896-1973) (Larumbe ; 13)
Fotografía de Joaquín Maurín | Bibliografía: p. XVII